An experimental analysis of a Y section exhaust manifold system with improved engine performance. (30th June 2008) - Seenikannan, P.; Periyasamy, V.M.; Nagaraj, P.
This study was undertaken to provide the knowledge necessary for raising the thermal efficiency and improving the performance of an engine by modifying the exhaust manifold (Y section). This paper investigates the effect of using various models of exhaust manifold on CI engine performance and exhaust emission. A four-stroke, six-cylinders, CI engine was used for conducting this study. In this study, the existing model and designed models are tested using real engine measurements. The benefits and limitations of these approaches are examined and compared.